Hepatic Vein Thrombosis in a COVID-19 Patient with Hereditary Thrombophilia: A Case Report - Chedid, Georges; Khoury, Rita; Noureldine, Hussein A; Gerges Harb, Jad; Tannoury, Esther; Semaan, Sahar; Elias-Rizk, Tamina; Ghanem, Hady (International Journal of Clinical Research, 2022)
Background: COVID-19 is an infection secondary to the novel SARS-COV-2 virus with a well-established increased risk for thrombotic events. However, the interaction between COVID-19 and other patient-specific hereditary or acquired thrombophilias remains a poorly explored area. Case Presentation: We herein report a case of a 23-year-old Caucasian female with known risk factors for coagulopathy (smoking, oral contraceptives, anti-phospholipid (aPL) antibodies, heterozygous Factor V Leiden mutation, and homozygous methylenetetrahydrofolate reductase (MTHFR) mutation) who developed a Budd-Chiari syndrome after testing positive for COVID-19. To our knowledge, this is the first report of a case of splanchnic vein thrombosis in a COVID-19 patient with the above risk factors. Conclusion: Such a presentation underscores the additional increased thrombotic risk attributed to COVID-19 infections in the setting of underlying hereditary or acquired thrombophilias.